2019
DOI: 10.7759/cureus.5457
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia Associated with Thiazide Diuretics in Hypertensive Adults

Abstract: IntroductionThiazide diuretics are essential first-line anti-hypertensive drugs which not only maintain blood pressure but also reduce stroke and congestive heart failure associated with morbidity and mortality in hypertensive patients. However, thiazide diuretics are associated with elevated serum uric acid (SUA) levels. This study aimed to evaluate the impact of thiazide diuretic use on their SUA levels among hypertensive individuals of Pakistan.MethodsIn this cross-sectional, prospective study, adult hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
1
8
0
3
Order By: Relevance
“…Also, subjects who took anti-hypertensive medication have significantly associated with hyperuricemia in which the likely hood of developing hyperuricemia were 11.56 higher in participants with medication when compared with counterparts. This was in line with studies conducted in Tunisia, Seychelles and Pakistan [19,29,30]. The association might be dues to the fact that medications especially diuretics, angiotensin converting enzyme inhibitors and beta-…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Also, subjects who took anti-hypertensive medication have significantly associated with hyperuricemia in which the likely hood of developing hyperuricemia were 11.56 higher in participants with medication when compared with counterparts. This was in line with studies conducted in Tunisia, Seychelles and Pakistan [19,29,30]. The association might be dues to the fact that medications especially diuretics, angiotensin converting enzyme inhibitors and beta-…”
Section: Plos Onesupporting
confidence: 90%
“…However, despite achieving adequate control a rise in blood pressure, these drugs are also associated with adverse events like hyperuricemia. Diuretics, beta-blockers and angiotensin converting enzyme inhibitors are associated with elevated serum uric acid by increasing direct urate reabsorption in the proximal renal tubules and by inhibited basolateral organic anion transporters and by reducing glomerular filtration rate [5,29]. The current study also showed that higher BMI and being centrally obese had significantly associated with hyperuricemia (AOR: 11.56, 95%CI: (3.94, 23.80)) and (AOR: 6.87, 95%CI: (2.53, 18.63)) respectively.…”
Section: Plos Onementioning
confidence: 99%
“…It is important to note that certain hypertension medications such as thiazide diuretics have been shown to increase uric acid concentrations. 18…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, thiazide diuretics are frequently used in geriatric patients with hypertension (7). However, thiazide diuretics are known to cause SUA elevation (8). The correlation between the Mini Mental State Examination (MMSE) and SUA has been studied previously, but the results have been contradictory (9).…”
Section: Introductionmentioning
confidence: 99%